Bibliometric and visualized analysis of posterior chamber phakic intraocular lens research between 2003 and 2023 - Ning, Jiliang; Zhang, Qiaosi; Liang, Wei; Zhang, Rui; Xing, Zequn; Jin, Lin; Zhang, Lijun (Frontiers in Medicine, 2024)
Introduction Myopia is causing a major public health concern, with its prevalence increasing globally. This study aimed to discuss posterior chamber phakic intraocular lens (pIOL) research publication trends and hotspots over the past 20 years. Methods Bibliometric analysis was performed using the Web Science Core Collection to investigate posterior-chamber pIOL research publication trends. The extracted records were analyzed, and a knowledge map was built using VOSviewer v.1.6.20. The analysis included visualizing the annual publication count, countries/regions distribution, international and institutional collaborations, author productivity, and journal contribution, in addition to identifying knowledge bases and hotspots. Burst keywords were extracted using CiteSpace v.6.1.R. Results In total, 791 articles on posterior chamber pIOLs published between 2003 and 2023 were retrieved. China had the highest number of publications, whereas Japanese papers received the most citations. Fudan University had the highest number of publications, with articles from Kitasato University having the highest number of citations. Regarding individual research, Xingtao Zhou has published the most significant number of articles, and Shimizu Kimiya had the highest number of citations. The top productive/influential journal was ‘Journal of Cataract & Refractive Surgery’. The top cited references primarily focused on reporting the clinical outcomes of implantable collamer lens (ICL) for individuals with moderate to high myopia. The keywords primarily formed four clusters: posterior chamber pIOL clinical outcomes for myopic astigmatism correction, posterior chamber pIOL implantation complications, ICL size selection and postoperative vault predictions, and postoperative visual quality following posterior chamber pIOL implantation. Conclusion This study presents the first bibliometric analysis of research trends in posterior chamber pIOL over the past two decades. We investigated the current state and emerging trends of global collaboration and research focal points in this field, offering fresh insights and guidance for researchers.